Multi-centre audit to determine factors associated with success and failure in treating colonic obstruction with self expanding metals stents (SEMS). (13th March 2011) - Geraghty, J; McMahon, M; Conlin, A; Alam, S; Gledhill, T; Estabragh, Z; Hill, J; Lee, S; Carlson, G; Martin, D; O'Toole, P; Ramesh, J; et al.
Abstract : Introduction: UK cancer guidelines recommend patients with malignant colonic obstruction are considered for stenting either as a bridge to curative surgery or as a palliative procedure. Considerable variation in practice persists due to lack of expertise, technical difficulties and hazards associated. Reported series include only small numbers so true success rates are unclear. Our aim is to determine outcomes following colonic stenting and factors associated with complications. Methods: All colonic stents inserted for large bowel obstruction in 5 North-West Teaching hospitals between 2005 and 2010 were audited retrospectively for outcomes including relief of obstruction, survival, complications and re-intervention. Results: 334 patients had stents inserted (mean age 71 years, mean ASA grade III) for palliation (76%), bridge to surgery (15.5%) and other indications (8.5%) (mostly benign strictures). Procedural success was 86%, with immediate complication rate of 14% due to: inability to deploy (6%), intraprocedural perforation (2.7%), malposition (0.6%), migration (2%), insufficient expansion (1%) and peri-interventional morbidity (1.2%). Technical success did not vary by indication (p=0.4) but using a through-the-scope (TTS) technique (65% of procedures) produced a higher success rate than radiological placement (93% v 80%; p=0.01) with fewer complications (12% v 20%; p=0.05). Perforation rates were lower for operators performing >20 procedures (p=0.04). Tumour position (above or below splenic flexure) did not affect success (p=0.3) or complications (p=0.6). 64% for palliation required no further intervention but 21% underwent subsequent colostomy and 5 perforated. 75% of 'bridge' patients had a single stage primary anastomosis. 30-day mortality was 14.6% for palliative group, 7.7% for bridge group, 17% for benign obstruction and 33% for extra–colonic malignant obstruction. Conclusion: This large audit reports similar problems to published smaller series but suggests that experienced operators using a TTS technique achieved better outcomes. High re-intervention rate in palliative stenting was disappointing. Significant mortality for extra-colonic malignant obstruction and benign strictures suggests that stenting should be carefully considered for these indications.